The Retranslation of Intertextuality: Paul Auster’s New York Trilogy - İrem Ceren Doğan (İstanbul Üniversitesi Çeviribilim Dergisi)
Intertextuality is a concept that has emerged in postmodernism and since become an integral part of postmodern theory. It refers to how each text is shaped by its relationship with other texts, as well as to the cultural and historical contexts in which it was produced. Postmodernism questions the notion that a text has a singular, objective meaning, suggesting that each text can be interpreted in multiple ways. This study approaches the translation of intertextuality by examining the intertextual connections in the first and retranslations. The corpus of this study is composed of the famous works of Paul Auster, an American postmodernist writer, namely "City of Glass," "Ghosts," and "The Locked Room" known as the “New York Trilogy”. This study aims to analyze the dynamics of retranslation of postmodern literature to present a different understanding of retranslation contrary to the retranslation hypothesis asserted by Berman (1990), Bensimon (1990), and Gambier (1994) as it seems outdated. As postmodernism is a contemporary movement of literature, the first and retranslations of the prevalent narrative techniques require a different understanding from the traditional point of view. This different understanding is related to contemporary approaches to retranslation asserted by Kaisa Koskinen, Outi Paloposki, Tahir Gürçağlar, and Siobhan Brownlie. In the comparative analysis of the examples taken from the “New York Trilogy,” the methodology of Hatim and Mason (2001) is utilized.